Evaluation and Preparation of a Designed Kartogenin Drug Delivery System (DDS) of Hydrazone-Linkage-Based pH Responsive mPEG-Hz-b-PCL Nanomicelles for Treatment of Osteoarthritis - Su, Wen-Ta; Huang, Ching-Cheng; Liu, Hsia-Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA) is a chronic disease caused by the damage of articular cartilage. Kartogenin (KGN) is a well-recognized small molecule which could induce MSCs chondrogenesis and promote cartilage repair treatments. Nano-level micells could be a suitable drug carrier technology for the treatments. In this study, the acid-responsive methoxy poly(ethylene oxide)-hydrazone-poly(ε-caprolactone) copolymers, mPEG-Hz-b-PCL, were synthesized. The structure was characterized by 1H NMR. The evaluation of a designed kartogenin drug delivery system (DDS) of hydrazone-linkage-based pH responsive mPEG-Hz-b-PCL nanomicelles for treatment of osteoarthritis could be carried out.